Haemostatic Effects of Recombinant Human Erythropoietin in Chronic Haemodialysis Patients - Geet, Chris van; Hauglustaine, Didier; Verresen, Luc; Vanrusselt, Marleen; Vermylen, Jos (Thrombosis and Haemostasis, 1989)
Recombinant human erythropoietin was administered for up to 40 weeks to nine patients on chronic haemodialysis. From the third week of administration onwards, not only haemoglobin and haematocrit but also the platelet count rose, the latter, however, transiently. Subnormal platelet aggregation before therapy also improved transiently and in parallel with the erythropoietin dosage. The bleeding time normalized in almost all patients. There were no major side-effects. We conclude that recombinant erythropoietin improves haemostasis in chronic haemodialysis patients by increasing the haematocrit and in addition transiently enhances platelet number and function.
Keywords: Recombinant human erythropoietin; Chronic haemodialysis patients; Bleeding time; Platelet